2022
DOI: 10.1038/s41467-022-33832-6
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized fusion inhibitory peptide protects cynomolgus macaques from measles virus infection

Abstract: Measles is the most contagious airborne viral infection and the leading cause of child death among vaccine-preventable diseases. We show here that aerosolized lipopeptide fusion inhibitor, derived from heptad-repeat regions of the measles virus (MeV) fusion protein, blocks respiratory MeV infection in a non-human primate model, the cynomolgus macaque. We use a custom-designed mesh nebulizer to ensure efficient aerosol delivery of peptide to the respiratory tract and demonstrate the absence of adverse effects a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…We hypothesized that mAb 77, like the Nipah mAbs 2B12 and 1H1, inhibits viral entry by binding to prefusion F before it has been activated by H-receptor engagement on the target cell. This mechanism differs from that of HRC peptide mimics, which interact with the F protein only after activation of fusion, when the virus has attached to the cell membrane, but before fusion has been completed ( 83 , 84 ). Unexpectedly, however, our mechanistic assays demonstrated that mAb 77 does not block any initiation of conformational change.…”
Section: Discussionmentioning
confidence: 94%
“…We hypothesized that mAb 77, like the Nipah mAbs 2B12 and 1H1, inhibits viral entry by binding to prefusion F before it has been activated by H-receptor engagement on the target cell. This mechanism differs from that of HRC peptide mimics, which interact with the F protein only after activation of fusion, when the virus has attached to the cell membrane, but before fusion has been completed ( 83 , 84 ). Unexpectedly, however, our mechanistic assays demonstrated that mAb 77 does not block any initiation of conformational change.…”
Section: Discussionmentioning
confidence: 94%